Penentuan Lama Waktu Kelembapan Tanah sebelum Panen yang Memengaruhi Rendemen Tebu - Elda Nurnasari; . Djumali (Jurnal Ilmu Pertanian Indonesia, 2019)
The duration of soil moisture greatly determine the sugarcane content. Until now the effect of soil moisture duration on the sucrose content have not been studied. The objective of this study was to evaluate the duration of soil moisture before harvest that determines the yield of various types of sugarcane maturity rates. The research was conducted at Village Karangploso Malang starting from July 2015-October 2016. A factorial experiment was arranged in Randomized Block Design with 3 replications. The first factor consisted of 9 duration of average of soil moisture (1.0 week; 0.5; 1.0; 1.5; 2.0; 2.5; 3.0; 3.5; and 4.0 months) before harvesting. The second factor consisted of 4 varieties/clones (Bululawang, PS 06 199, Kenthung, and PS 881). The results showed that sugar cane plants required the duration of soil moisture in the range of 1.5-4.0 months before harvesting depending on the variety/clones. Bululawang variety (late maturity), PS 06 199 (middle to late maturity), Kenthung variety (early to middle maturity), and PS 881 varieties (early maturity) each required an average of 60,23% soil moisture during 3.0-3.5 months, 70.00% for 3.0 months, 81.40% for 2.5-4.0 months, and 86.25% for 2.0-3.5 months before harvesting to obtain the optimum sucrose content.